Post-vaccination symptoms of covishield vaccine among frontline workers of a tertiary care center in Pathanamthitta District - Sahya S Dev; Saritha Susan Vargese; Serah Mamachan; Abraham V Varghese; Elsheba Mathew (Wolters Kluwer Medknow Publications, 2023)
Introduction: The COVID-19 pandemic, which began in late 2019 and is still ongoing, has affected health and life across the world. Widespread vaccination with highly effective vaccines is an important tool in the efforts to control this pandemic. To determine post-vaccination symptoms after the first dose of Covishield vaccine among health care workers at a tertiary care centre in Pathanamthitta District.Materials and Methods: A descriptive cross-sectional study in a tertiary care hospital in Pathanamthitta District. Data on adverse effects following vaccination with the first dose of Covishield vaccine were collected from health care workers through online surveys and interviews. Baseline characteristics were described with frequency, percentages, and mean. Associations between categorical variables were assessed using the Chi-square test. Results: Of the 1,115 health care workers who participated in the study, the majority were medical students (28.3%), followed by nurses (24.8%), and doctors (19.1%). Post-vaccination symptoms were reported by the majority of the participants (95.1%). The most common symptoms were pain at the site of injection (79.8%), followed by myalgia (67.2%), and tiredness (64.6%). Hospitalization was required for six (0.5%) of the participants. Conclusion: The symptoms reported in the study were those already known to be the general side effects associated with vaccines. The information obtained from this study will aid in health promotion activities related to COVID-19 vaccination.